Properties of Controlled-Release-Water-Retention Fertilizer Coated with Carbonaceous-g-Poly(acrylic acid-co acrylamide)Superabsorbent Polymer - Suriati, Ghazali; Saidatul Shima, Jamari; N., Noordin; Tan, K. M. (IACSIT Press, 2017)
Fertilizer and water are very important in determining the production of agriculture nowadays. Apart of that, the excessive use of fertilizer in plantation somehow could leads to environmental pollution. The present study reported a preparation of controlled release water retention (CRWR) fertilizer coated with superabsorbent polymer (SAPs). The purpose of coating the fertilizer using SAPs is to enhance the utilization of fertilizer and reduce the environmental pollution. In this study, the synthesis of carbonaceous-SAPs was carried out via solution polymerization technique by using monomers of poly(acrylic acid) (AA) and acrylamide (AM), cross linker of methylene bisacrylamide (MBA) and initiator of ammonium peroxodisulfate (APS) that partially neutralized with sodium hydroxide (NaOH). The fertilizer granule then was coated with carbonaceous-SAPs which later known as CRWR fertilizer. The morphology and the bonding formation of the CRWR fertilizer were investigated by using Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectrophotometer (FTIR), respectively. Moreover, the water absorbency and water retention in soil were conducted in order to investigate the efficiency of carbonaceous-SAPs on the properties of CRWR fertilizer. Based on the results, it was found that the CRWR fertilizer coated with carbonaceous-SAPs had higher water absorbency and water retention ability than the CRWR fertilizer without carbonaceous-SAPs. The addition of the carbonaceous filler in the formulation of SAP increase the water uptake compared to unfilled-SAP. Moreover, types of soil also play an important factor in water retention properties. CRWR fertilizer in organic soil results in higher water retention ability compared in top soil.